Investigação do estado de aderência em revestimentos de tubos metálicos utilizando parâmetros modais visando aplicação a poços de petróleo - Nobrega, Marcilene Vieira da (2010)
Oil wells may be as deep as 5000 m and consist of several types of casing. As these casings are cast in place, there is an annular space that needs to be filled to support the whole system and protect the metallic tubes against substances present in the environment of the well. This process is accomplished through cementing, by pumping a paste composed mainly of water, cement and additives. Various events such as variations in pressure and temperature, vibrations caused by explosive charges applied in the well and migration of undesirable substances in the interface casing/sheath of cement paste can impair the quality of the bond between the metallic coating and the sheath of cement paste.Specifically substances such as NaCl and oil can seep into this interface and interfere with the bond. This reflects in the operation of the well. This work aimed investigating the behavior of the condition of bond of the interface casing/sheath of cement paste, through modal tests. For this investigation modal tests were carried out on samples molded with metal pipes coated partially by a cylinder of cement paste and three contact conditions were simulated: no treatment on the surface of the pipes, treatment with NaCl and with oil. It was observed that the presence of these substances affects the modal parameters natural frequency and damping ratio and consequently affect the condition of bond, identified by the value of an elastic spring constant (K), inserted at the interface from a numerical model developed to investigate the phenomenon. It was also observed that the employed technique is sensitive to changes in adhesion at the interface metal tube / sheath of cement paste.